(untitled) (Journal of Pharmaceutical Negative Results, 2014)
Objective: To study the anthelmintic activity of Artabotrys hexapetalus (Linn.f) leaves.Materials and Methods: The extraction was made using the hydroalcohol withsoxhlet extraction system. The hydroalcoholic extract of varying concentration wasused for conducting anthelmintic activity (12.5, 25, 50 and 100 mg/ml). Eudriluseugeniae (African adult earthworm) was used as the test organism. Result: Thetime of paralysis and death of the earthworms, the positive control (albendazole)was more effective and no effect was shown by the hydroalcoholic extract of varyingconcentrations. Conclusion: Hydroalcoholic extract of Artabotrys hexapetalus, didn’tshow any anthelmintic activity at the concentration of 12.5, 25, 50 and 100 mg/ml.